Pengaruh Semangat Kerja Dan Kedisiplinan Terhadap Kinerja Karyawan PT. Omron Manufacturing Of Indonesia - Daspar, Daspar; Rismawati, Rismawati (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Employee performance in company will not always be stable because in the factors of production there is a role of human resources which can change due the certain factors. Researchers conducted pre-research on what factors that can employee performance and they obtained the top three aspects, namely work spirit, discipline and compensation. This research aims to determine wheter work spirit and discipline affect the employee performance of PT. Omron Manufacturing of Indonesia. The kind of research that used is quantitative research. The sampling technique used is saturated sampling technique by making all populations 80 people at thermoset section of PT. Omron Manufacturing of Indonesia as the samples. Data collection techniques used are observation, distributing questionnaires and library research. The data analysis method used is data quality test, classic assumption test and test hypothesi. The research was processed using SPSS version 25.0 for windows in T test shows that Work Spirit has a significant effect on employee performance because it has a sig. value 0,000 < 0,005, Discipline has no a significant effect on employee performance because it has a sig. value 0,462 > 0,005, and Compensation has no significant effect on employye performance because it has a sig. value 0,196 > 0,005. As for the F test result has a significant value of 0,000 < 0,005 which means Ho is rejected and Ha is accepted, meaning that simultaneously the variables of Work Spirit, Discipline have a significant effect on employee performance.